Prominence-Interpretation Theory: Membangun Kredibilitas Perusahaan di Media Digital - Putri Neva Lumeta; Irwansyah Irwansyah (Jurusan Sastra Indonesia, Fakultas Sastra, Universitas Negeri Malang (UM), 2018)
In this time of information is searchable and reachable, companies need to be more aware of their reputation and credibility online.Users always have the tendency of recheck and double check. In other occasions, users are looking for certain or needed information online or to a specific sites or company’s assets. It can be company’s websites, social media, forum, or simply search engine. Using prominence-interpretation theory, companies can be aware of their digital or online credibility evaluated by users. The theory explains and very much can be expanded to cope with current situation of credibility evaluation through various platforms online.Keyword: Prominence-interpretation theory, strategic communication, social media